The effect of new business formation on regional development over time: the case of Germany - Michael Fritsch; Pamela Mueller (Technische Universität Bergakademie Freiberg, Fakultät für Wirtschaftswissenschaften, 2006)
We investigate the effects of new business formation on employment change in German regions. A special focus is on the lag-structure of this effect and on differences between regions. The different phases of the effects of new business formation on regional development are relatively pronounced in agglomerations as well as in regions with a high-level of labor productivity. In low-productivity regions, the overall employment effect of new business formation activity might be negative. The interregional differences indicate that regional factors play an important role.
Keywords: M13; O1; O18; R11; 330; Entrepreneurship; new business formation; regional development; Unternehmensgründung; Unternehmer; Regionale Entwicklung; Lag-Modell; Schätzung; Deutschland